Common Fixed Points of a Finite Family of I-Asymptotically Nonexpansive Mappings by S-Iteration Process in Banach Spaces: Birol Gunduz, Sezgin Akbulut - Team, Support (Thai Journal of Mathematics, 2017)
In this paper, we consider S iteration process to aproximate the common fixed point of a finite family of I-Asymptotically naonexpansive mapings in Banach spaces. We also study the different convergence creteria of S iteration process under suitable conditions. It presents some new results in this paper.